The effects of motivation on international tourists’ destination loyalty: Satisfaction as the mediator - Mahadzirah, Mohamad; Mutia Sobihah, Abd Halim; Zainudin, Awang; Nur Izzati, Ab Ghani (2017)
The purpose of this study was to examine the relationships among motivation, tourist's satisfaction and destination loyalty. Surveys were conducted among international tourists using a systematic sampling method. A total of 380 questionnaires answered completely and the data were analyzed using Structural Equation Modelling (SEM). The results revealed, satisfaction fully mediated the relationship between pull motivation and destination loyalty. Satisfaction was not a mediator in the relationship between push motivation and destination loyalty. The push motivation was measured by two dimensions, gaining knowledge and relaxation. The pulling factors were related to the tangible features, the attractions of Terengganu. The implications of the study revealed that promotional strategy should take into account the push motivation factors and prepare destination's attributes that matched the current and future demand.